Improvement of solar still with chemical potential (International Journal of Food and Nutritional Sciences, 2021)
In this chapter explains the chemical potential implemented through pyramid stepped basin solar distiller (PSBSD). They analyzed the different temperature components based on the behavior of the distill process. Different parameter analysis is suitable via to explain the performance of the solar still. It also explains the liquid to vapor phase equilibrium the distillate system. They achieved the 38.135% & 4.280 l/m2 per day.